Penentuan diagnostik reference level (drl) lokal proyeksi thorax pa pada modalitas radiografi umum villa s.m di instalasi radiologi rsi unisma malang - Auliaa, Amatullah Al (Maliki Interdisciplinary Journal, 2024)
DRL (Diagnostic Reference Level) is a tool to estimate the appropriate dose without harming the patient. This study aims to determine the local DRL value in Pa thorax examination at RSI Unisma Malang. Determination of the local DRL value based on INAK and ESAK parameters, the DRL value is obtained from the second quartile of INAK and ESAK values. The results obtained from this research show that the local DRL value of the INAK parameter is 0.12 mGy and the local DRL value calculated from the ESAK parameter is 0.16 mGy. From these results, it can be said that the dose received by patients at the thorax examination at RSI Unisma Malang has complied with the BAPETEN standard.